KORELASI ANTARA KADAR HEMOGLOBIN, FERITIN SERUM, DAN SOLUBLE TRANSFERRIN RECEPTOR PADA ANAK USIA 6-59 BULAN - , dr. Fajar Diah Tri Kusumastuti; , Prof. Dr. dr. Sutaryo, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Early detection of iron deficiency before anemia in early children especially beyond 6-59 months become important due to its impact to permanent neurocognitive development disorder. Bone marrow aspiration with Prussian blue staining was not routinely done because of the invasive procedure. Hemoglobin is unsensitive tool for iron deficiency without anemia and serum ferritin influenced by infection and inflammation. Soluble transferrrin receptors (sTfR) is a sensitive marker for detecting iron deficiency state but is not used widely in daily practice. Objective: to determine the correlation between hemoglobin level, serum ferritin, and soluble transferrin receptor in early children 6-59 months. Methods: This cross sectional study was performed in 6-59 months old children who visited POSYANDU in Yogyakarta and Bantul districs that choosen by cluster sampling. Anamnesis, anthropometric and physical examination was performed. Inclusion criteria were health children appropiate with anamnesis and examination results. Children who received iron supplementation we excluded. After fulfilled the informed consent, amount subjects are 85 children. After that, blood sample was collected to examined hemoglobin, serum ferritin, and soluble transferrin receptor level. Results: Spearman correlation test showed a significant correlation between hemoglobin level and serum ferritin level and also between hemoglobin level and sTfR with coefficient correlation respectively r= -0,220 (p=0,043), r= -0,317 (p=0,003). Coefficient correlation between serum feritin level and sTfR was r=- 0,033 (p=0,767). Statistically, the correlation is not significant. Conclusion: The increase level of hemoglobin will correlate with the decrease level of serum ferritin and sTfR. Meanwhile, the increase level of serum ferritin will correlate with the decrease level of sTfR.